Analisis Buku Jendela Dunia dalam Buku Bahasa Indonesia untuk Kelas V Berdasarkan BSNP: Penelitian - Filza Halisatul Aufa; Nasywa Iga Danuarta; Reza Olivia; Farizka Yumna Khoirunnisa; Arasyid Syahbani; Panca Dewi Purwati (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to analyse the feasibility instrument of the book Indonesian Language: Moving Together for Grade V Elementary School, especially in Chapter 2 "World Window Book", according to the BSNP reference. The method used is descriptive qualitative with document review techniques, identifying the quality of book content, language quality, presentation quality and display or graphic quality. The results of the analysis showed that: (1) the content aspect of the book covers almost all fiction and nonfiction text material according to Curriculum 2013 and has been updated in the last five years; (2) the language aspect meets the Enhanced Indonesian Spelling Edition V and uses a straightforward and easy to understand style; (3) the presentation aspect presents complete exercises at the end of the chapter that are interesting and motivate students to discuss, write creatively, and read comprehension; (4) the graphical aspect uses standard font sizes and illustrations that support the visualisation of the text. Nevertheless, there are recommendations to add exercises to differentiate sentence structures and argumentation texts to improve students’ critical thinking skills.